Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar IPA Materi Peristiwa Alam pada Siswa Kelas V SDN 101742 Hamparan Perak T.A. 2023/2024 - Puspitasari, Evi; Ramadhani, Mastari; Harahap, Syarifah Ainun (Medan Resource Center, 2024)
This study aims to examine the effect of the Mind Mapping learning model on the academic performance of fifth-grade students at SDN 101742 Hamparan Perak. The research focuses on comparing the effectiveness of the Mind Mapping model used in the experimental class with the conventional learning model applied in the control class. The study involved a total of 62 students, with 33 students in class Va and 29 students in class Vb. A quasi-experimental design was employed, and the data were analyzed using the Polled Variance formula. The results indicated a significant difference in student learning outcomes between the two groups. The t-count value was 6.121, which is greater than the t-table value of 1.67 at a 5% significance level, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). Additionally, the N-Gain value of 0.49 demonstrates a medium improvement in learning outcomes for the experimental group, confirming the effectiveness of the Mind Mapping model compared to the conventional approach.